Adipocyte-Derived Versican and Macrophage-Derived Biglycan Control Adipose Tissue Inflammation in Obesity - Han, Chang Yeop; Kang, Inkyung; Harten, Ingrid A.; Gebe, John A.; Chan, Christina K.; Omer, Mohamed; Alonge, Kimberly M.; den Hartigh, Laura J.; Gomes Kjerulf, Diego; Goodspeed, Leela; Subramanian, Savitha; Wang, Shari; et al. (Cell reports (Cambridge), 2020)
Obesity is characterized by adipose tissue inflammation. Because proteoglycans regulate inflammation, here we investigate their role in adipose tissue inflammation in obesity. We find that adipose tissue versican and biglycan increase in obesity. Versican is produced mainly by adipocytes and biglycan by adipose tissue macrophages. Both proteoglycans are also present in adipose tissue from obese human subjects undergoing gastric bypass surgery. Deletion of adipocyte-specific versican or macrophage-specific biglycan in mice reduces macrophage accumulation and chemokine and cytokine expression, although only adipocyte-specific versican deletion leads to sustained improvement in glucose tolerance. Macrophage-derived biglycan activates inflammatory genes in adipocytes. Versican expression increases in cultured adipocytes exposed to excess glucose, and adipocyte-conditioned medium stimulates inflammation in resident peritoneal macrophages, in part because of a versican breakdown product, versikine. These findings provide insights into the role of adipocyte- and macrophage-derived proteoglycans in adipose tissue inflammation in obesity. [Display omitted] •Versican derives from adipocytes in obese adipose tissue•Adipose tissue macrophages are the major source of biglycan in obesity•Adipocyte-specific ablation of versican attenuates inflammation and insulin resistance•Macrophage-specific deficiency of biglycan improves adipose tissue inflammation Proteoglycans have many functions, including providing a scaffold and regulating the inflammatory response. In this study, Han et al. show that adipose tissue proteoglycans affect inflammation and insulin resistance as a result of crosstalk between versican produced by adipocytes and biglycan produced by macrophages.